Nexus between renewable energy consumption, economic growth, and CO2 emissions in Algeria: New evidence from the Fourier-Bootstrap ARDL approach - Elbadri, Marei; Bsikre, Salah; Alamari, Osama; Balcilar, Mehmet (Wiley, 2023)
Governments often impose new energy strategies to support new CO2 emission-reducing technologies without affecting economic growth. Hence, this study aims to re-investigate the relationship between economic growth, renewable energy use, and CO2 emissions in Algeria from 1990 to 2018. Motivated by the mixed findings of the existing literature, which ignore the Fourier function and bootstrap test and apply the newly developed Fourier bootstrap autoregressive distributed lag model (FARDL). Our findings indicate that renewable energy use and growth have a long-run relationship with CO2 emissions and do not accept the existence of the Environmental Kuznets Curve (EKC) hypothesis for CO2 emissions in Algeria. In the long term, the results show that renewable energy use has a negative and significant impact, and growth has a positive and statistically significant effect on CO2 emissions. In the short run, the findings indicate that renewable energy use reduces CO2 emissions, while both the growth and squared growth had positive and statistically insignificant impacts on CO2 emissions, confirming the lack of evidence supporting the EKC hypothesis. Moreover, the causality test indicates a one-way causation from growth to renewable energy use, confirming the conservation hypothesis for Algeria and from growth to CO2 emissions. Interestingly, we found one-way causality from CO2 emissions to renewable energy use, attributing this to the fact that renewable energy usage has yet to reach a point that it can significantly cause a CO2 emissions reduction. Based on the results, we recommend that policymakers design appropriate policies to decarbonize energy consumption, e.g., increasing fossil fuel costs and implementing a carbon tax. In contrast, Algeria should promote new CO2 emission-reducing technologies without affecting economic growth, e.g., tax exemptions and reductions for enterprise owners in the renewable energy industry.
Keywords: Algeria; ARDL model; CO2 emissions; economic growth; Fourier bootstrap; renewable energy